2019
DOI: 10.1038/s41564-019-0462-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for inhibition of Plasmodium vivax invasion by a broadly neutralizing vaccine-induced human antibody

Abstract: The most widespread form of malaria is caused by Plasmodium vivax. To replicate, this parasite must invade immature red blood cells, through a process which requires interaction of the Plasmodium vivax Duffy binding protein, PvDBP with its human receptor, the Duffy antigen receptor for chemokines, DARC. Naturally acquired antibodies that inhibit this interaction associate with clinical immunity, suggesting PvDBP as a leading candidate for inclusion in a vaccine to prevent malaria due to Plasmodium vivax. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(149 citation statements)
references
References 56 publications
5
144
0
Order By: Relevance
“…In a recent study, ten human monoclonal antibodies (mAbs) from a PvDBP-immunized volunteer were cloned and tested for their blocking activity using the DBP-DARC interaction. One mAb potently inhibited invasion in vitro using P. knowlesi parasites expressing P. vivax DBP ( Rawlinson et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, ten human monoclonal antibodies (mAbs) from a PvDBP-immunized volunteer were cloned and tested for their blocking activity using the DBP-DARC interaction. One mAb potently inhibited invasion in vitro using P. knowlesi parasites expressing P. vivax DBP ( Rawlinson et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both candidates induced strain-transcending functional antibodies measured in vitro. Using human mAbs generated through vaccination or natural vivax exposure, structural studies have identified functional and non-functional epitopes that will provide a rational basis to improve the design of PvDBP immunogens 103,104 .…”
Section: Transmission-blocking Vaccinesmentioning
confidence: 99%
“…mAb 2C6 epitope: 265 K – F 486 (dark green box), highlighting critical contact residues. mAb DB9 epitope: 476 D – E 503 (magenta box), highlighting critical contact residues [ 33 ]. mAb 3C9 epitope: 476 D – E 493 (green box), highlighting critical contact residues [ 55 ] HARBPs 1635: 398 R – G 417 (purple), 1637: 438 S – F 457 (light green) and 1639: 478 L –R 497 (apricot) located in neutralizing epitopes’ SD3 region [ 56 ].…”
Section: Plasmodium Vivax and Its Main Receptormentioning
confidence: 99%
“…Critical interaction regions between parasite ligands and host cell receptors have been defined from the structures of two of the most important Plasmodium species worldwide: P. falciparum and P. vivax . This has also enabled identifying functional and non-functional epitopes from ligand-neutralizing and/or inhibitory antibody (Ab) complexes [ 29 , 30 , 32 , 33 ]. Combining both approaches (receptor-ligand and antigen-antibody) highlights small ligand regions which are critical for parasite invasion, i.e., hotspots; these can be used for the rational design of future vaccines components or treatment against malaria infection.…”
Section: Introductionmentioning
confidence: 99%